RELEVANSI NILAI INFORMASI AKUNTANSI DI BURSA EFEK INDONESIA - Susi Dwimulyani (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2010)
This research is designed to examine the value relevance of accounting information at Indonesian Stock Exchange for 2003-2007. Research samples were selected from all of emitent listing in Indonesian Stock Exchange from 2003 — 2007. For hypotesis testing were used Francis and Schipper, and Brown model. There were two multiple regression equation. The research sample are all listed companies at Indonesian Stock Exchange for 2003-2007 that had publised financial statements at December 31. Based on E-Views program, it was found first cross sectional regression : p-value 0,00 and average R2 0,5637, it means that there was strong relationship between fair value of companies and its book value. The second regression was found that p-value 0,00 and average R2 0,8458, it means that there was strong relationship between book value equity of companies and its operating income. Based on statistical calculation, it was concluded that value relevance of accounting information was very important for investor and creditor for their decision.